Performan Ayam yang Diberi Pakan Additive - I GEDE WEMPI DODY SURYA PERMADI; Risqa Novita; Ririen Indriawaty Altandjung; Gunawan (Jurnal Sains Peternakan, 2023)
ABSTRACT Broiler chickens (broilers) are very popular as chickens for consuming animal protein because they are easy to maintain and only take about one month for broiler chickens to be consumed. Chicken farm management such as DOC, housing systems, maintenance and feed systems are critical points in farm management. Feed is the biggest cost in livestock management. The increase in the price of corn causes an imbalance in the output and input of livestock management. In addition to a source of corn substitute chicken feed, researchers are also developing additive feed as additional feed to fulfill protein and crude fiber. This writing uses a systematic review method based on journal articles, theses, theses and books on chicken feed and feed additives. The keywords used in the selection of articles are chicken feed journals, feed additives. Google schoolar and pop 8 win database are used for browsing articles on the internet